2015
DOI: 10.1128/mcb.00636-14
|View full text |Cite
|
Sign up to set email alerts
|

MondoA-Mlx Transcriptional Activity Is Limited by mTOR-MondoA Interaction

Abstract: Mammalian target of rapamycin (mTOR) integrates multiple signals, including nutrient status, growth factor availability, and stress, to regulate cellular and organismal growth. How mTOR regulates transcriptional programs in response to these diverse stimuli is poorly understood. MondoA and its obligate transcription partner Mlx are basic helix-loop-helix leucine zipper (bHLHZip) transcription factors that sense and execute a glucose-responsive transcriptional program. MondoA-Mlx complexes activate expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…Interestingly, mTOR has been shown to negatively regulate MondoA, a basic helix-loop helix leucine zipper transcription factor that functions in an obligate heterodimer with Mlx. The MondoA-Mlx interaction is suppressed by mTOR activation (44), and is one of two transcriptional complexes known to regulate TXNIP expression (43,45). To determine whether MondoA-Mlx was regulating TXNIP transcription in this therapeutic context, MondoA expression was ablated using pooled siRNAs that target the gene that encodes MondoA, MLXIP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, mTOR has been shown to negatively regulate MondoA, a basic helix-loop helix leucine zipper transcription factor that functions in an obligate heterodimer with Mlx. The MondoA-Mlx interaction is suppressed by mTOR activation (44), and is one of two transcriptional complexes known to regulate TXNIP expression (43,45). To determine whether MondoA-Mlx was regulating TXNIP transcription in this therapeutic context, MondoA expression was ablated using pooled siRNAs that target the gene that encodes MondoA, MLXIP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is counter-intuitive that TXNIP protein would accumulate in the presence the translation initiation inhibitor RocA and following knockdown of EIF4E; however, TXNIP undergoes both cap-dependent and IRES-dependent translation (32). Our previous studies demonstrated that mTORC1 suppresses MondoA transcriptional activity and TXNIP expression by competing for its obligate transcriptional partner Mlx (19). Consistent with our previous findings, the mTORC1 inhibitor Torin increased TXNIP expression, but this increase was much more modest than that observed with CHX ( Figure 1H).…”
Section: Translation Inhibition Drives Txnip Expressionmentioning
confidence: 99%
“…MondoA-dependent ( Figure 6A-B Cancer cells must coordinate the use and the availability of nutrients to support growth and division. TXNIP is a potent negative regulator of glucose uptake, in fact its loss or downregulation is sufficient to increase glucose uptake (19,40), suggesting that low TXNIP levels may be a common route to aerobic glycolysis common in cancer. Consistent with this hypothesis, TXNIP levels are generally lower in tumors compared to normal adjacent tissues (8), and a number of pro-growth/oncogenic pathways suppress TXNIP expression by a variety of mechanisms (19,20,35,(41)(42)(43).…”
Section: Protein Synthesis Inhibition Drives G6p Productionmentioning
confidence: 99%
“…Thus, the MondoA-TXNIP axis constitutes a negative feedback loop that regulates glucose homeostasis (15, 25, 26). Our previous work established that the MondoA-TXNIP axis is downregulated by PI3K, mTOR or Myc activation, which contributes to their well characterized activities in driving aerobic glycolysis (20, 27, 28). TXNIP is also subject to post-translational regulation in response to signaling pathways.…”
Section: Introductionmentioning
confidence: 99%